Embracing Epistemic Humility: Confronting Triumphalism in Three Abrahamic Religions - Borchert, Donald (Lexington Books, 2013)
Embracing Epistemic Humility: Confronting Triumphalism in Three Abrahamic Religions builds a case that encourages advocates of world views, especially the children of Abraham—Jews, Christians and Muslims—to embrace an attitude of epistemic humility toward their world views and thereby defeat the triumphalism which, on the contemporary scene, has infected the world views of all too many in the Abrahamic tradition. Triumphalists see their world view as the ultimate repository of spiritual truth: all other world views are inferior and their adherents need to be converted forcefully, or silenced, or destroyed to prevent their cancerous views from metastasizing.Embracing such epistemic humility is not only the antidote to triumphalism but it is also a powerful motivator to transform world view competitors into comrades engaged in a struggle to combat evil and to promote human flourishing.